Saving, Risk Sharing, and Preferences for Risk - Mazzocco, Maurizio (American Economic Review, 2004)
Saving decisions are made jointly by household members who generally earn risky incomes. Consequently, to interpret saving patterns it is crucial to analyze the relationship between intra-household risk sharing and intertemporal choices. To that end in this paper the household is characterized as a group of agents with possibly heterogeneous preferences making efficient decisions. Two results are obtained. First, it is shown that risk sharing can increase the amount saved by the household. Second, I find that an increase in risk aversion and prudence of an individual member can reduce household risk aversion and prudence. These results are consistent with the empirical evidence collected using the HRS. 1